2015
DOI: 10.3171/2014.9.jns1461
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcomes following traumatic Grade 3 and 4 vertebral artery injuries: a 10-year retrospective analysis from a Level I trauma center. The Parkland Carotid and Vertebral Artery Injury Survey

Abstract: ObJect Grade 3 and 4 blunt vertebral artery (VA) injuries may carry a different natural course from that of lower-grade blunt VA injuries. Proper screening, management, and follow-up of these injuries remain controversial. Grade 3 and 4 blunt VA injuries were analyzed to define their natural history and establish a rational management plan based on lesion progression and cerebral infarction. MetHODS A retrospective review of a prospectively maintained database of all blunt traumatic carotid and vertebral arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…5,8,10,13 While some reports have marginalized the clinical consequences of these strokes, often identifying asymptomatic or functionally insignificant areas of ischemia, 10,15 others have described significant morbidity and mortality. 12 Our series supports the latter with 7 of 10 strokes being symptomatic, including 2 deaths directly attributable to vertebrobasilar ischemia.…”
Section: Vertebrobasilar Ischemiasupporting
confidence: 78%
See 3 more Smart Citations
“…5,8,10,13 While some reports have marginalized the clinical consequences of these strokes, often identifying asymptomatic or functionally insignificant areas of ischemia, 10,15 others have described significant morbidity and mortality. 12 Our series supports the latter with 7 of 10 strokes being symptomatic, including 2 deaths directly attributable to vertebrobasilar ischemia.…”
Section: Vertebrobasilar Ischemiasupporting
confidence: 78%
“…10 Scott et al reported a stroke rate of 7.1% but hypothesized that the cerebral infarcts occurred in the immediate postinjury period and thus were present on admission. 12 The current series also failed to identify a significant difference in the use of antiplatelets between patients with and without stroke. Future investigation should focus on novel therapies for the management of traumatically occluded VAs; possibilities include dual antiplatelet therapy, systemic anticoagulation, and endovascular intervention.…”
Section: Future Directionmentioning
confidence: 69%
See 2 more Smart Citations
“…TVAI is a potentially devastating injury. First described by Matas in 1893 (1), TVAI often affects the young following road traffic accidents, hanging and sporting injuries and the mortality rate may be as high as 100% (2). Despite this, TVAI is notoriously difficult to diagnose (3).…”
Section: Introductionmentioning
confidence: 99%